Nâo se nasce homem, torna-se homem: performatividades do masculino em uma barbearia - Pauli Tomazetti, Tainan; Marconi, Dieson; Machado, Alisson (Cuestiones de Género: de la igualdad y la diferencia, 2018)
From an observation in an upper middle-class barber shop in the city of Porto Alegre, Rio Grande do Sul, Brazil, the article reflects about the male performativities and the articulation of an ethics and an aesthetics linked to the masculinity notion developed in this space. Relating the observed meanings of these practices, we demonstrate the way in which masculinity is related to the nature of men, concealing the performative procedures and discursive effects by which it is produced. Although highly regulated, self-care work indicates shades of sense disputes over traditional masculinities, even though they do not postpone disruptions to the dominant and prescriptive model of heteronormativity.